O lugar da mulher na Ciranda de Pedra: um estudo sobre a representação feminina no romance de Lygia Fagundes Telles - Amanda Damasceno Batista (2022)
This dissertation analyzes the romance Ciranda de Pedra, by Lygia Fagundes Telles, through the perspective of the relationship between the work and the historical and sociological context of the time, especially with regards to women’s space. It also discusses how female authorship impacts the construction of the novel and its specificities when compared to male writing. The novel’s technical aspects were discussed through authors such as Ligia Chiappini Leite and Alfredo Leme Carvalho. Reviews made by Carlos Drummond de Andrade, Alfredo Bosi, and Antonio Candido were used to analyze the book. Besides, the works of Elza Berquó and Carla Pinsky were used for understanding the relationship between the narrative and what was happening in the country at the time of the novel’s release. This dissertation also presents the particularities of women’s writing and especially Lygia’s writing, based on her testimonies. This was done through the study of female literature by several authors, mainly by Regina Dalcastagné. In this way, this study explores why the work was written as it was, which includes the fact that the author is a woman who writes about women.